Successful Management of Nitrite Poisoning in Crossbred Dairy Calves - E, Niyas; Simon, Shibu; Banglavan, Surej Joseph; Mathew, Jith John; Das, Ani S.; John, Reni; Reshma, S. (Indian Journal of Animal Nutrition, 2020)
Nitrate/ Nitrite poisoning in dairy cattle occurs when there is an abrupt change in diet from the introduction of a bulk feed source with high nitrate levels. Over fertilization of fodder with untreated manure and occurrence of drought season followed by a rainy season could precipitate a higher the level of nitrate in plants. A sudden onset of illness was reported in eight crossbred dairy calves between 8-11 months of age at University Livestock Farm and one among the affected calf died after showing symptoms of discomfort, excessive salivation, tympany, dyspnoea, sternal recumbency progressing to lateral recumbency, pedalling movements and stiffness of the limbs and neck. On clinical examination, the affected animals exhibited sialorrhoea, tympany, increased pulse and respiratory rates, laboured breathing, brownish discoloration of mucous membrane and loss of balance. Microscopical examination of rumen fluid revealed normal protozoan motility. Blood colour was dark chocolate brown in all the affected animals and coagulation time was delayed. Animals had a history of adlibitum feeding with chopped lush green fodder grasses namely Hybrid Napier and fodder Maize that were harvested from cattle slurry irrigated fodder plots. Based on the history and clinical signs noticed, the case was presumptively diagnosed as nitrate/nitrite poisoning, later confirmed with diphenylamine test. All the animals were treated with intravenous administration of 1 per cent methylene blue @ 1-2mg/kg BW. Subsequently the dairy calves showed an uneventful recovery from the condition.